Historical Atlas of the World - Published by Rand McNally (Skokie, Il Historical Atlas of the World, 1997)
The Historical Atlas of the World is made up of more than 100 colorful maps that present periods and turning points in world history. The atlas also features a how-to-use section. Recommended by Laura Berquist Syllabus Grades 5, 7 and 8, Kolbe Academy Grades 4-8, Seton Grade 10, Seton High School History, Seton High School Geography Author: Rand McNally Grade 6+ Number of Pages: 113 Paperback Publisher: Rand McNally ISBN 0-528-83969-1
Includes Map and Index.
Keywords: Historical geography -- Maps